Lola Cendales, Alfredo Ghiso, Santiago Gómez, Marco Mejía, Piedad Ortega, Mario Peresson, Jorge Posada y Alfonso Torres. Paulo Freire y Orlando Fals Borda - Barrera Rivera, Dan Abner (2026)
Lola Cendales, Alfredo Ghiso, Santiago Gómez, Marco Mejía, Piedad Ortega, Mario Peresson, Jorge Posada y Alfonso Torres. Paulo Freire y Orlando Fals Borda